2022
DOI: 10.3390/brainsci12121658
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebro-Cerebellar Effective Connectivity in New-Onset Juvenile Myoclonic Epilepsy

Abstract: (1) Objective: Resting-state fMRI studies have indicated that juvenile myoclonic epilepsy (JME) could cause widespread functional connectivity disruptions between the cerebrum and cerebellum. However, the directed influences or effective connectivities (ECs) between these brain regions are poorly understood. In the current study, we aimed to evaluate the ECs between the cerebrum and cerebellum in patients with new-onset JME. (2) Methods: Thirty-four new-onset JME patients and thirty-four age-, sex-, and educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…Combining the node reduction methods, we found that abnormal discharges originating from six brain regions i.e., Tha, Cere, BG, SMC, VC, and PFC are most likely to lead to epileptic seizure symptoms in patients with JME during resting state. The conclusion in the current study is the same as that of the anterior study, but the former is more comprehensive (Vollmar et al, 2012;Lee and Park, 2019;Qin et al, 2019;Ma et al, 2022). After incorporating the independence of white matter fiber tracts and brain interval FC in the network analysis, we found that the core network also had a certain ability to resist abnormal discharges due to their dynamic change and that the three subcortical brain regions, namely, Tha, Cere, and BG formed a highly coupled subnetwork of functional connections.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Combining the node reduction methods, we found that abnormal discharges originating from six brain regions i.e., Tha, Cere, BG, SMC, VC, and PFC are most likely to lead to epileptic seizure symptoms in patients with JME during resting state. The conclusion in the current study is the same as that of the anterior study, but the former is more comprehensive (Vollmar et al, 2012;Lee and Park, 2019;Qin et al, 2019;Ma et al, 2022). After incorporating the independence of white matter fiber tracts and brain interval FC in the network analysis, we found that the core network also had a certain ability to resist abnormal discharges due to their dynamic change and that the three subcortical brain regions, namely, Tha, Cere, and BG formed a highly coupled subnetwork of functional connections.…”
Section: Discussionsupporting
confidence: 66%
“…Using the first node reduction method, we found that patients with JME have 21 different brain functional connectivity networks in the resting state. After running the code 500 times, we observed that these 21 different types of connection networks were distributed between ( Abe et al, 2007 ; Vollmar et al, 2012 ; Chin and Ratnavelu, 2016 ; Poleon and Szaflarski, 2017 ; Lee and Park, 2019 ; Qin et al, 2019 ; Ma et al, 2022 ; Samandari Bahraseman et al, 2022 ; Huang et al, 2023 ; Ke et al, 2023 ). As the number of runs increased, the probability of each type of connection network appearing gradually approached 1/21.…”
Section: Resultsmentioning
confidence: 99%
“…The cerebellum was found to be involved in the production of several types of myoclonus [7], and its pathological involvement has been demonstrated in benign adult familial myoclonic epilepsy (BAFME) [8], juvenile absence epilepsy [9], and nonconvulsive partial status epileptic [10]. Previous studies suggested that the cerebellum is involved in the pathophysiological mechanisms of JME [11][12][13]. And it has been hypothesized that the increased inhibition effect of the cerebellum on the (basal ganglia related thalamocortical) BTC pathway might potentially contribute to the motor symptoms in patients during seizures [14].…”
Section: Introductionmentioning
confidence: 99%